A new species group of Trisinus Raffray (Coleoptera: Staphylinidae: Pselaphinae), with description of two new species from the Tianmu Mountains, China - Ding, Mei-Lin; Niu, Xiao-Ling; Yin, Zi-Wei (Zootaxa, 2025)
Two closely related species of the genus Trisinus Raffray that exhibit exaggerated cephalic excavations are described: T. cavernosus Ding, Niu & Yin, sp. nov. from Tianmushan National Nature Reserve and T. qingliangmontis Ding, Niu & Yin, sp. nov. from Qingliangfeng National Nature Reserve. Detailed illustrations of the habitus and important diagnostic features are presented for both species to facilitate reliable identification. Based on the shared male characteristics, a new species group within Trisinus is termed and defined.